2014
DOI: 10.1053/j.gastro.2014.08.032
|View full text |Cite
|
Sign up to set email alerts
|

PI3K Regulation of RAC1 Is Required for KRAS-Induced Pancreatic Tumorigenesis in Mice

Abstract: Background & Aims New drug targets are urgently needed for the treatment of pancreatic ductal adenocarcinoma (PDA). Nearly all PDAs contain oncogenic mutations in the KRAS gene. Pharmacologic inhibition of KRAS has been unsuccessful, leading to a focus on downstream effectors that are more easily targeted with small molecule inhibitors. We investigated the contributions of phosphoinositide 3 kinase (PI3K) to KRAS-initiated tumorigenesis. Methods Tumorigenesis was measured in the KrasG12D/+;Ptf1aCre/+ mouse m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
99
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(104 citation statements)
references
References 39 publications
5
99
0
Order By: Relevance
“…Pik3ca ablation and chronic inhibition led to up-regulation of AKT signaling, possibly resulting from compensatory activity from other PI3K isoforms. In contrast, Pik3ca ablation significantly diminished both Rac1 activity and expression in Kras mutant pancreatic cells, accompanied by significant inhibition of Kras-activated Rac1 guanine exchange factors Tiam1 and Vav1 [69]. Pancreas-specific ablation of Rac1 has the same phenotype as Pik3ca ablation in Kras mutant mice [68,69], indicating the PI3K/RAC axis plays an important role in Kras-driven pancreatic tumor development.…”
Section: Expression Of Mutant Krasmentioning
confidence: 94%
See 2 more Smart Citations
“…Pik3ca ablation and chronic inhibition led to up-regulation of AKT signaling, possibly resulting from compensatory activity from other PI3K isoforms. In contrast, Pik3ca ablation significantly diminished both Rac1 activity and expression in Kras mutant pancreatic cells, accompanied by significant inhibition of Kras-activated Rac1 guanine exchange factors Tiam1 and Vav1 [69]. Pancreas-specific ablation of Rac1 has the same phenotype as Pik3ca ablation in Kras mutant mice [68,69], indicating the PI3K/RAC axis plays an important role in Kras-driven pancreatic tumor development.…”
Section: Expression Of Mutant Krasmentioning
confidence: 94%
“…In contrast, Pik3ca ablation significantly diminished both Rac1 activity and expression in Kras mutant pancreatic cells, accompanied by significant inhibition of Kras-activated Rac1 guanine exchange factors Tiam1 and Vav1 [69]. Pancreas-specific ablation of Rac1 has the same phenotype as Pik3ca ablation in Kras mutant mice [68,69], indicating the PI3K/RAC axis plays an important role in Kras-driven pancreatic tumor development. Similarly, Stat3 phosphorylation is found to occur at multiple stages of Kras 12D -driven pancreatic tumorigenesis but not in normal pancreatic tissue [76,77].…”
Section: Expression Of Mutant Krasmentioning
confidence: 94%
See 1 more Smart Citation
“…In the PI3K pathway, studies have consistently shown that, among the major kinase subunits of PI3K, p110α, but not p110β, is the major oncogenic KRAS effector to activate PI3K and promote tumor growth of PDAC and multiple other cancer types (Gupta et al 2007;Baer et al 2014;Gritsman et al 2014;Wu et al 2014). The essential role of the PI3K pathway is supported by additional genetic studies showing that oncogenic Kras-driven PDAC development is abolished upon deletion of Pdk1, the central downstream kinase mediating PI3K signaling (Eser et al 2013).…”
Section: Kras Signaling Surrogates In Tumor Development and Maintenancementioning
confidence: 99%
“…One can therefore ask the question of the use of targeted therapies in this context, including those targeting the PI3K/AKT pathway [2]. Indeed, the lipid kinase PI3Kα was shown to drive pancreatic cancer initiation downstream the main driving oncogene of this cancer [3][4][5][6], oncogenic Kras, found mutated in more than 80% of all pancreatic cancer patients.…”
Section: Introductionmentioning
confidence: 99%